Locke, Anger and the State - Numao, Kei (Passion: Journal of the European Philosophical Society for the Study of Emotions, 2024)
While “anger” or “angry” are words often used to describe today’s societies and politics, they are not the ones commentators of Locke use when talking about his political theory. This article argues that anger is in fact at the heart of his political outlook, and that focusing on the passion helps us to see an important aspect of the state. Since little has been said in relation to Locke and anger, the article starts by examining how he defined, viewed and justified anger. The article shows how Locke conceptualized a problematic component of anger, revenge, in terms of retributive punishment, which, when proportionate, can be viewed positively. The article then shows how Locke placed and tamed anger in the hands of the state to solve the inconveniences that exist in the state of nature caused by it. The article thus sheds light on the state’s role as an anger manager.